Kemampuan Literasi Sains Siswa Kelas IV Pada Materi Gaya Melalui Pembelajaran Berbasis Proyek Berbantuan Zoom Meeting - Madina, Tasya; Aeni, Ani Nur; Sujana, Atep (Jurnal Pena Ilmiah, 2021)
The application of the Project Based Learning (PjBL) is the right way to improve students' scientific literacy. The purpose of this study was to determine the implementation of project-based learning assisted by zoom meetings and to determine the scientific literacy skills of fourth grade students on style materials through project-based learning assisted by zoom meetings. The research method used is descriptive quantitative with the research subjects used are fourth grade students at SDN Tegalkalong. Data was collected by observing teacher performance and student activities and testing scientific literacy skills. The results of the study are the average percentage of teacher performance obtained as a whole is 98% which is included in the criteria for the success of very good teacher performance. Then the average value of student activity as a whole is 81.3 which is included in the criteria for the success of very good teacher performance. And for the scientific literacy ability, students get an overall average score of 77.4 which is included in the criteria for good success. It can be said that the project-based learning model assisted by the zoom meeting can have a significant effect on the literacy skills of grade IV students in style material and have a good impact on teacher performance and student activities.